Epidemiological survey on tick borne diseases of pet dogs in korla, northwestern china - Jianhui CHEN; Shen SHI 2; Nannan CUI; Lixin SU; Ziqi WANG; Fang LI; Shang ZHAN; Guoyu ZHAO; Yuanzhi WANG; Xijiang WANG (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Pet dogs pose a potential risk to transmitting zoonotic pathogens by ticks. However information about the prevalence status in pet dogs of tick-borne diseases is currently limited. In this study, 196 blood samples and 223 ticks were collected from pet dogs in Korla, northwestern China. Based on morphological and molecular characteristics, all ticks were identified as Rhipicephalus turanicus sensu stricto. We used primers targeting the 16S ribosomal (16S rRNA) gene for detection of Anaplasma bovis species, targeting the small subunit 18S ribosomal RNA(18S rRNA) gene for detection of Hepatozoon canis species and targeting htpAB-associated repetitive element gene (IS111) for detection of Coxiella burnetii species The nested PCR(nPCR)-positive products were sequenced, aligned, and phylogenetically analyzed. three tick-borne pathogens were detected in the samples. Coxiella burnetii were detected both in parasitic ticks and in blood samples with a detection rate of 17.93% (40/233) in tick and 79.1% (155/196) in blood samples, followed by 21.52% H. canis (48/233) in tick, 2.5% A. bovis (5/196) in blood samples. This study provided molecular evidence for the occurrence of A. bovis, H. canis and C. burnetii circulating in pet dogs and their ticks in northwestern China. Understanding the prevalence of Tick-borne diseases in pet dog is essential for developing effective strategies for disease control and management.